Regulation of γδ T Cell Effector Diversification in the Thymus - Parker, Morgan E.; Ciofani, Maria (Frontiers in Immunology, 2020)
γδ T cells are the first T cell lineage to develop in the thymus and take up residence in a wide variety of tissues where they can provide fast, innate-like sources of effector cytokines for barrier defense. In contrast to conventional αβ T cells that egress the thymus as naïve cells, γδ T cells can be programmed for effector function during development in the thymus. Understanding the molecular mechanisms that determine γδ T cell effector fate is of great interest due to the wide-spread tissue distribution of γδ T cells and their roles in pathogen clearance, immunosurveillance, cancer, and autoimmune diseases. In this review, we will integrate the current understanding of the role of the T cell receptor, environmental signals, and transcription factor networks in controlling mouse innate-like γδ T cell effector commitment.